What to do when you're new : how to be confident, comfortable, and successful in new situations - Rollag, Keith (AMACOM, 2016)
What to Do When You're New combines the author's research with that of leading scientists to explain why we are so uneasy in new situations-and how we can learn to become more confident and successful newcomers. Blending stories and insights with simple techniques and exercises, this one-of-a-kind guide will get you out of your comfort zone and trying new things in no time.